7*a-2*5-2*6*a+5=

Simple and best practice solution for 7*a-2*5-2*6*a+5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7*a-2*5-2*6*a+5= equation:


Simplifying
7a + -2 * 5 + -2 * 6a + 5 = 0

Multiply -2 * 5
7a + -10 + -2 * 6a + 5 = 0

Multiply -2 * 6
7a + -10 + -12a + 5 = 0

Reorder the terms:
-10 + 5 + 7a + -12a = 0

Combine like terms: -10 + 5 = -5
-5 + 7a + -12a = 0

Combine like terms: 7a + -12a = -5a
-5 + -5a = 0

Solving
-5 + -5a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -5a = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -5a = 0 + 5
-5a = 0 + 5

Combine like terms: 0 + 5 = 5
-5a = 5

Divide each side by '-5'.
a = -1

Simplifying
a = -1

See similar equations:

| x^2+7x+10=(x+5)(x+2) | | 5y-7=2y+11 | | 4+8+4+2=4396 | | 4+3+9+6=5482 | | .40x+.90(600)=.60(800+x) | | x^4+2x^3+3x^2+x+2=0 | | 6(2x-7)+6=12x-36 | | 39-5x=13x+19 | | -a^2+20a-60=0 | | 25x^2+10x+1=7 | | 16x^2-8x+1=11 | | x=4y*1.2 | | x^2-6x+9=9 | | 34=10+4q | | 5s^2+23s+24=0 | | -2X^2+14X+196=0 | | a+a=a | | 2q+2=-12 | | 4x^2+28X=240 | | 2x-4=x+9 | | (x-2)(3x+8)=0 | | ln(x)+ln(x-6)=ln(16) | | (50-4y)+(25-2x)=100 | | -36+2w=8w+w | | 7X-8X-9X+2+3+17X=12 | | 111111111111111111111(a)= | | -x-4=16 | | -10=6+2c | | 5.25+x=3.75 | | b+5=-13 | | x-(x*0.2)=9.6 | | 23=x-17 |

Equations solver categories